1994
DOI: 10.1029/93ja02103
|View full text |Cite
|
Sign up to set email alerts
|

Midlatitude detection of ELF whistlers

Abstract: Narrow‐band, whistlerlike magnetic events distinguished by nearly monochromatic signals decreasing in frequency with time have been observed for the first time at midlatitudes in the ELF band. Measurements performed during September 3 to October 5, 1985 at Table Mountain, California (34.4°N, 117.7°W), show that the frequency and dispersion characteristics of these events are similar to events detected at auroral latitudes (Heacock, 1974), including a narrow‐band magnetic signal monotonically decreasing in freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(42 citation statements)
references
References 25 publications
6
32
4
Order By: Relevance
“…The maximum number of events observed around 09:00 to 10:00 h (IST) which is consistent with the low latitude observation by Wang et al (2005). There appears to be a night to dawn gap, the same as that reported by Heacock (1974), Sentman and Ehring (1994) or Wang et al (2005). There also appears an increased rate of occurrence from 20:00-23:00 h (IST), but no other peak is observed as reported by Wang et al (2005) from low latitude.…”
Section: Observationssupporting
confidence: 87%
See 4 more Smart Citations
“…The maximum number of events observed around 09:00 to 10:00 h (IST) which is consistent with the low latitude observation by Wang et al (2005). There appears to be a night to dawn gap, the same as that reported by Heacock (1974), Sentman and Ehring (1994) or Wang et al (2005). There also appears an increased rate of occurrence from 20:00-23:00 h (IST), but no other peak is observed as reported by Wang et al (2005) from low latitude.…”
Section: Observationssupporting
confidence: 87%
“…Two and more whistlers closely associated in time, but having different sources are known as multiflash whistlers while a whistler with two or more components, each of which have traversed a different path through the ionosphere is known as multipath whistler (Helliwell, 1965). These events are similar to those observed previously at mid and low latitude by Sentman and Ehring (1994) and Wang et al (2005) in some aspects but no observation report multiflash nature of ELF whistlers. Also they are very short in duration and have a dispersion resembling terrestrial (VLF) whistlers contrary to the previously reported ELF whistlers.…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations